Planning of Detailed Engineering Design (DED) for the Tourist Area Around Bukit Lembah Subur Village Lake in Pelalawan Regency Based on Community Involvement - Wahyu Hidayat; Muhd. Arief Al Husaini; Mashuri; Sri Djuniati; Ahmad Nawawi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Recreation or traveling is one of human's inner needs. We can use anything that has tourism potential as a tourist destination. The artificial lake in the Bukit Lembah Subur Village has the potential to be developed into a tourist destination. In designing tourist attractions, detailed engineering design (DED) is required to facilitate the work of building tourist attractions. The aim of this service is to design and also create a DED for the artificial lake tourist area in Bukit Lembah Subur Village. The method used is through observation, discussion, planning and output help to develop tourist areas. The result of community service activities is that they can complete the DED for the artificial lake tourist area in Bukit Lembah Subur Village so that it can help with the planning and development of the tourist area.